Is Video-Assited Thoracoscopic Surgery Superior to Limited Axillary Thoracotomy in the Management of Spontaneous Pneumothorax? - Meaghen J Hyland; Ahmad S Ashrafi; André Crépeau; Reza J Mehran (Canadian Respiratory Journal)
OBJECTIVE: To evaluate bullectomy and pleurectomy in the treatment of spontaneous pneumothorax (PNO) using video-assisted thoracoscopic surgery (VATS), and to compare the outcome with that of the same procedure performed using limited axillary thoracotomy (LAT).